Nutrient management of shallot (Allium cepa Aggregatum group) in Riau peatlands, a pot experiment - Sopha, Gina Aliya; Aprianto, Fahmi (Brawijaya University, 2024)
Peatland degradation might affect peatland functions. Sustainable agriculture practice, i.e., nutrient management, is one of the efforts that could be made to delay the degradation. Therefore, this research aimed to identify the best nutrient management practice for shallot production in degraded peatlands. A split-plot experimental design was performed in a greenhouse environment, with cultivars (Sembrani and Trisula) as the main plot and eleven combinations of NPK fertilizer as the subplot. All treatments received 4.4 t ha-1 dolomite to increase the soil pH. Results showed that Sembrani produced a higher bulb yield than Trisula. Trisula was sensitive to acidic soils and failed to yield a high bulb. The NPK recommended dose for Sembrani was 150 kg N ha-1, 100 kg P2O5 ha-1, and 100 kg K2O ha-1, producing 57.50 g plant-1 equal to 14.4 t ha-1 or 53% higher than the control (without NPK). Meanwhile, growing Trisula was not recommended for peatlands.